The Role of Subject Teacher Working Group (MGMP) Management in Improving Teacher Performance: A Multisite Study - Tutut Sulistiani; Ahmad Thohirin; Suyitno Suyitno (The Future of Education Journal, 2026)
The Subject Teacher Consultation Group (Musyawarah Guru Mata Pelajaran/MGMP) serves as an important professional development forum that contributes to improving the quality of teaching and learning. However, the effectiveness of MGMP implementation is highly dependent on systematic organizational management and support from various stakeholders. This study aims to describe the management processes of MGMP, analyze the factors influencing its implementation, and examine its implications for improving teacher performance through a multi-site study conducted at SMPN 1 Pasrepan and SMPN 2 Kejayan, Pasuruan Regency. This research employed a qualitative approach using a multi-site study design. Data were collected through observations, in-depth interviews, and documentation involving school principals, MGMP coordinators, local language teachers, and students. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal that MGMP management was implemented systematically through the stages of planning, organizing, implementation, and evaluation. Supporting factors for successful MGMP implementation included teachers’ commitment, support from school principals, collaboration among teachers, and the availability of facilities and infrastructure. Meanwhile, inhibiting factors consisted of limited time, insufficient operational funding, uneven participation among members, and the mismatch between teachers’ educational backgrounds and the subjects they taught. The implementation of MGMP management had positive implications for enhancing teachers’ professional and pedagogical competencies, strengthening collaboration among teachers, improving the quality of instruction, and supporting the preservation of local languages. The study also found that the alignment of MGMP programs with teachers’ professional needs and strong leadership support from school principals were key determinants in improving teacher performance.